Microbiota Is Involved in Post-resection Adaptation in Humans with Short Bowel Syndrome - Gillard, Laura; Mayeur, Camille; Robert, Véronique; Pingenot, Isabelle; Le Beyec, Johanne; Bado, André; Lepage, Patricia; Thomas, Muriel; Joly, Francisca (Frontiers in Physiology, 2017)
Short bowel syndrome (SBS) is characterized by severe intestinal malabsorption following restrictive surgery. The objective of this study was to determine the functional contribution of SBS-microbiota after resection. It is well known that SBS-microbiota displayed specific features with a prevalence of Lactobacillus, a low amount of some anaerobic microbes (Clostridium leptum) and an accumulation of fecal lactate in some patients. Patients with jejuno-colonic anastomosis were stratified according to the presence of lactate in their feces and, we observe that the lactate-producing bacteria were predominant in the sub-group of patients accumulating fecal lactate. One case of D-encephalopathy crisis occurred when the D- lactate isoform accumulated in the feces and plasma bicarbonate levels decreased. The fecal sample at the time of the encephalopathy was transferred to germ free rats (SBS-H rats). The SBS-H microbiota conserved some characteristics of the SBS donnor, predominated by lactate-producing bacteria (mainly Lactobacillus), a low level of lactate-consuming bacteria and undetectable C. leptum. However, lactate did not accumulate in feces of recipient rats and the D-encephalopathy was not reproduced in SBS-H rats. This suggests that the intact small bowel of the recipient rats protected them from lactate accumulation and that D-lactate encephalopathy can occur only in the absence of small intestine. After fecal transfer, we also show that gnotobiotic rats exhibited high levels of circulating GLP-1 and ghrelin, two hormones that are known to be induced in SBS patients. Therefore, the microbiota of SBS is a reservoir of biological signals involved in post-resection adaptation.